Psychological appraisal of spirituality indices of crash helmet phobia among Nigerians (2008)
This study examined the spirituality factors associated with crash helmet phobia among motorcycle cyclists and consumer of their success in Nigeria. The study randomly selected 1,327 participants across 5 major cities in Nigeria. These are Ibadan, Lagos, Kaduna, Kano and Enugu. They consist of 862 commercial motorcyclists and 465 customers who responded to the Crash Helmet Scale. The survey uses a nationally representative probability sample selected using an extended form of the two-stage random-digit selection procedure. The survey employed a rotating panel design to gather data from approximately 200 respondents on a weekly basis. Results showed that 56.9% of the participants refused use of crash helmet because they believe people could use the avenue to charm helmets for various evil machinations such as money ritual. Also, 75.7% stated that the use of helmet could not prevent accident most of the time. Majority of the commercial cyclists and customers (93.2%) averred that the helmet is not convenient for them. The findings were highly essential since they raise awareness about the relevance of cultural reality in the treatment of helmet phobia among Nigerians and the need for re-orientating the motorcycle cyclists and customers in Nigeria.